Analýza spokojenosti zákazníků KomTeSa, spol. s r.o. a návrhy opatření na zvýšení jejího zvýšení - Menšíková, Marie (Vysoké učení technické v Brně. Fakulta podnikatelská, 2015)
Diplomová práce se zabývá problematikou analyzování spokojenosti zákazníků s produkty a službami a její následnou aplikací na firmu KomTeSa, spol. s r.o. Cílem práce je vysvětlit podstatu, důležitost a význam této oblasti, analyzovat současnou úroveň zákaznické spokojenosti v konkrétní společnosti a formulovat možný způsob řešení, který by mohl pomoci této společnosti odstranit její slabé stránky a následně tak vést i k vyššímu zákaznickému uspokojení

The diploma thesis deals with the analyzing of customers' satisfaction with products and service in general, afterwards focusing on the following application on KomTeSa, Ltd. The goal of the diploma thesis is to explain the basis and importance of this field, to analyze concrete companies' level of their own customers' satisfaction and, in consequence, to define a possible solution that can help each company both eliminate its weaknesses and satisfy the clients better.
Customer Satisfaction Analysis of Company KomTeSa, spol. s r.o. and Recomentadions for its Improvement
Keywords: Spokojenost zákazníka; analýza spokojenosti zákazníka; nástroje a modely hodnocení spokojenosti zákazníka; marketingový výzkum.; Customer satisfaction; analysis of customer’s satisfaction; instruments and models of customer’s satisfaction evaluation; marketing research.